2019
DOI: 10.1080/14786419.2018.1543677
|View full text |Cite
|
Sign up to set email alerts
|

A new ocotillol-type ginsenoside from stems and leaves of Panax quinquefolium L. and its anti-oxidative effect on hydrogen peroxide exposed A549 cells

Abstract: A new ocotillol-type ginsenoside, namely 12-one-pseudoginsenoside F 11 (12-one-PF 11 ), was isolated from stems and leaves of Panax quinquefolium, whose structure was elucidated 6-O-[α-L-rhamnopyranosyl-(1-2)-β-D-glucopyranosyl]-dammar-12-one-20S,24R-epo xy-3β,6α,25-triol. 12-one-PF 11 significantly suppressed hydrogen peroxide induced oxidative stress in human lung carcinoma A549 cells. As compared with model group, 12-one-PF 11 improved cell viability of A549 cells in a dose-dependent manner, and significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Final DMSO concentration in the sample was less than 0.1%. Cell culture and MTT assay were done as we described previously to evaluate 24 h-incubation of triterpenoids or the 18 h-incubation of CSE on the cell viability of A549 cells [6].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Final DMSO concentration in the sample was less than 0.1%. Cell culture and MTT assay were done as we described previously to evaluate 24 h-incubation of triterpenoids or the 18 h-incubation of CSE on the cell viability of A549 cells [6].…”
Section: Methodsmentioning
confidence: 99%
“…Western blot assay was performed as previous described [6] to study the effects of ginsengenin-S2 on the protein expression of HDAC2 and Nrf2 in CSE-stimulated A549 cells. Anti-HDAC2 (#ab32117), anti-Nrf2 (#ab137550) and anti-β-actin (#ab137550) were from Abcam Company (Cambridge, UK).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ginsenosides, the main active ingredient in Panax ginseng, Panax quinquefolium , and Panax notoginseng , are often classified into four groups: Protopanaxadiol type, protopanaxatriol type, oleanane-type, and ocotillol-type [3,4]. Numerous studies have demonstrated that ginsenosides are the major active compounds of antioxidant, anti-obesity, anti-inflammation, neuroprotective, anti-tumor, anti-coagulant, and immunoregulatory effects in P .…”
Section: Introductionmentioning
confidence: 99%
“…Ginseng, the root of Panax ginseng Meyer, was a widely used folk medicine in many Asian countries including China, Korea, and Japan for a thousand years [12,13]. It was reported that ginseng extract G115, the standardized extract of Panax ginseng , exhibits an antidepressant effect in ethanol-treated mice models via increasing brain-derived neurotrophic factor (BDNF) levels in the hippocampus and prefrontal cortex [14].…”
Section: Introductionmentioning
confidence: 99%